Differential Association of Spirituality and Religiosity With Rumination: Implications for the Treatment of Depression. Issue 5 (May 2021) - Saunders, David; Svob, Connie; Pan, Lifang; Abraham, Eyal; Posner, Jonathan; Weissman, Myrna; Wickramaratne, Priya
Abstract : Abstract: Recent studies have shown that religiosity (R) is associated with lower rates of depression, whereas spirituality (S) is associated with higher rates. Rumination has also been associated with higher rates of depression. Some have hypothesized that rumination mediates the differential association of religiosity and spirituality with depression. We empirically test this hypothesis in a longitudinal, multigenerational sample through associations between rumination and depression, R/S and depression, and R/S and rumination. Cross-sectionally, total rumination scores were predicted by spirituality (standardized β = 0.13; 95% confidence interval [CI], 0.00–0.26), with subscale (reflection, depression, and brooding) standardized betas ranging from 0.11 to 0.15 (95% CI, −0.03 to –0.29). Cross-sectionally, rumination was not predicted by religiosity. Longitudinally, and consistent with previous findings, religiosity, but not spirituality, predicted reduced depressive symptoms (standardized β = −0.3; 95% CI, −0.58 to −0.01). The association between spirituality and rumination was driven by millennials. Psychotherapies that target rumination for depression might therefore be especially effective in the millennial demographic.